The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0100-204x2002001200013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of micronutrients on dry matter yield and interaction with other nutrients in annual crops

Abstract: -The objective of this work was to determine the influence of Zn, Mn and Cu on shoot dry matter yield and uptake of macro and micronutrients in upland rice, common bean and corn. Six greenhouse experiments were conducted using a Dark Red Latosol (Typic Haplusthox). Treatments consisted of application of Zn at 0, 5, 10, 20, 40, 80 and 120 mg kg -1 , of Mn at 0, 10, 20, 40, 80, 160, 320 and 640 mg kg -1 and of Cu application at 0, 2, 4, 8, 32, 64 and 96 mg kg -1 . Zinc increased yield of rice, Mn increased yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
15

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 17 publications
7
41
0
15
Order By: Relevance
“…The interaction between zinc and nitrogen was non-significant. The application of zinc also improved the leaf area per plant which might be due to the fact that zinc has role in proper functioning of photosynthetic enzymes (Fageria 2002). Our results confirm the investigation of Mehdi et al (2012) who suggested that application of 10 kg ha -1 zinc in maize fodder increases plant height and leaf area.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The interaction between zinc and nitrogen was non-significant. The application of zinc also improved the leaf area per plant which might be due to the fact that zinc has role in proper functioning of photosynthetic enzymes (Fageria 2002). Our results confirm the investigation of Mehdi et al (2012) who suggested that application of 10 kg ha -1 zinc in maize fodder increases plant height and leaf area.…”
Section: Resultssupporting
confidence: 90%
“…Nitrogen makes the plant succulent by absorbing more amount of water and increase the fresh weight but the effectiveness of zinc for increasing the dry biomass is clear from the results that zinc helped to increase dry biomass parallel with nitrogen. This is due the fact that zinc affects nitrogen uptake and its metabolism (Fageria 2002 Sharifi and Taghizadeh (2009) that zinc increased nitrogen uptake and nitrogen content due to synergistic effect which affect the protein formation. Zinc and nitrogen enhanced the percentage of crude protein which resulted in improvement in forage quality.…”
Section: Resultsmentioning
confidence: 99%
“…This cofactor role of micronutrients is crucial for enzyme and nonenzyme activities in plant metabolism under different environmental conditions (Table 2). For instance, Zn specifically plays a role in the enzymatic processes involved in the biosynthesis of the plant growth regulator, auxin (Hossain et al 1997;Fageria 2002). This is an important function given the role of auxins in enhancing root growth, with agronomic consequences in terms of allowing the plant greater ability to access nutrients and water.…”
Section: Physiological Roles and Roles In Abiotic And Biotic Stress Mmentioning
confidence: 99%
“…Significant variation in shoot dry weight among tropical legume cover crop species grown on Brazilian Oxisol has been reported by Fageria et al [10]. Similarly, response to Cu fertilization by legume crops grown in acidic Cerrado soils has been reported by Fageria [11] and Fageria [12]. Lucas and Knezek [13] reported that for responsive crops the Cu concentration should exceed 4 to 6 mg kg −1 for mineral soils and 20 to 30 mg kg −1 for organic soils.…”
Section: Shoot Dry Weightmentioning
confidence: 79%